2022
DOI: 10.1002/aelm.202200503
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Excellent Energy Storage Properties in Fine‐Grain High‐Entropy Relaxor Ferroelectric Ceramics

Abstract: ABO3‐type high‐entropy relaxor ferroelectric ceramics have rarely been studied in energy storage capacitor owing to easy formation of impurity phase. In this work, single phase (Bi0.2Na0.2Ba0.2Sr0.2Ca0.2)TiO3‐xmol%PbO high‐entropy ceramics are fabricated and investigated. The optimal composition of x = 2.0 shows a remarkable comprehensive energy storage performance with high recoverable energy density Wrec = 8.2 J cm–3, ultrahigh efficiency η = 92.2%, excellent temperature stability (Wrec = 4.4 J cm‐3 ± 4%, η … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…The decreased tan δ favors to reduce the energy loss as heat during charge–discharge process and thus improve E b 1 . To further confirm the improved dielectric relaxation properties, the modified Curie–Weiss law is widely employed based on the equation (Figure 3G) 13,16 : 1εnormalrbadbreak−0.28em1εr,maxgoodbreak=()TTmγC0.28em$$\begin{equation}\frac{1}{{{\varepsilon _{\rm{r}}}}} - \;\frac{1}{{{\varepsilon _{{\rm{r}},{\rm{max}}}}}} = \frac{{{{\left( {T - {T_{\rm{m}}}} \right)}^\gamma }}}{C}\;\end{equation}$$where γ and C are diffusion factor and constant, respectively. The γ value increases monotonically with increasing x , revealing the improved dielectric relaxation behavior quantitatively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decreased tan δ favors to reduce the energy loss as heat during charge–discharge process and thus improve E b 1 . To further confirm the improved dielectric relaxation properties, the modified Curie–Weiss law is widely employed based on the equation (Figure 3G) 13,16 : 1εnormalrbadbreak−0.28em1εr,maxgoodbreak=()TTmγC0.28em$$\begin{equation}\frac{1}{{{\varepsilon _{\rm{r}}}}} - \;\frac{1}{{{\varepsilon _{{\rm{r}},{\rm{max}}}}}} = \frac{{{{\left( {T - {T_{\rm{m}}}} \right)}^\gamma }}}{C}\;\end{equation}$$where γ and C are diffusion factor and constant, respectively. The γ value increases monotonically with increasing x , revealing the improved dielectric relaxation behavior quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased tanδ favors to reduce the energy loss as heat during charge-discharge process and thus improve E b . 1 To further confirm the improved dielectric relaxation properties, the modified Curie-Weiss law is widely employed based on the equation (Figure 3G) 13,16 :…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that high-entropy ceramics can be much better energy storage materials than traditional dielectric ceramics. [9][10][11] Recently, the energy storage performance of a high-entropy ceramic, 0.88(Bi 0.4 K 0.2 Na 0.2 Ba 0.2 )TiO 3 -0.12Sr(Mg 1/3 Nb 2/3 )O 3 Tianyu Liu and Bo Yan contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%